Impact of Severe Acute Respiratory Syndrome Coronavirus 2 Infection on Pregnancy Outcomes: A Population-based Study. (8th February 2021) - Crovetto, Francesca; Crispi, Fàtima; Llurba, Elisa; Pascal, Rosalia; Larroya, Marta; Trilla, Cristina; Camacho, Marta; Medina, Carmen; Dobaño, Carlota; Gomez-Roig, Maria Dolores; Figueras, Francesc; Gratacos, Eduard; et al.
Abstract: Background: We performed a population-based study to describe the impact of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection on pregnancy outcomes. Methods: This prospective, population-based study included pregnant women who consecutively presented at first/second trimester visits or at delivery at 3 hospitals in Barcelona, Spain. SARS-CoV-2 antibodies (immunoglobulin [Ig] G and IgM/IgA) were measured in all participants, and nasopharyngeal real-time polymerase chain reaction (RT-PCR) was performed at delivery. The primary outcome was a composite of pregnancy complications in SARS-CoV-2–positive vs negative women that included miscarriage, preeclampsia, preterm delivery, perinatal death, small-for-gestational-age newborn, or neonatal admission. Secondary outcomes were components of the primary outcome plus abnormal fetal growth, malformation, or intrapartum fetal distress. Outcomes were also compared between positive symptomatic and positive asymptomatic SARS-CoV-2 women. Results: Of 2225 pregnant women, 317 (14.2%) were positive for SARS-CoV-2 antibodies (n = 314, 99.1%) and/or RT-PCR (n = 36, 11.4%). Among positive women, 217 (68.5%) were asymptomatic, 93 (29.3%) had mild coronavirus disease 2019 (COVID-19), and 7 (2.2%) had pneumonia, of whom 3 required intensive care unit admission. In women with and without SARS-CoV-2 infection, the primary outcome occurred in 43 (13.6%) and 268 (14%), respectively (risk difference, –0.4%; 95% confidence interval, –4.1% to 4.1). Compared with noninfected women, those with symptomatic COVID-19 had increased rates of preterm delivery (7.2% vs 16.9%, P = .003) and intrapartum fetal distress (9.1% vs 19.2%, P = .004), while asymptomatic women had rates that were similar to those of noninfected cases. Among 143 fetuses from infected mothers, none had anti–SARS-CoV-2 IgM/IgA in cord blood. Conclusions: The overall rate of pregnancy complications in women with SARS-CoV-2 infection was similar to that of noninfected women. However, symptomatic COVID-19 was associated with modest increases in preterm delivery and intrapartum fetal distress. Abstract : In a large population based-study, the overall rate of pregnancy complications in all women with SARS-CoV-2 infection (symptomatic or asymptomatic) was similar to non-infected women. However, symptomatic COVID-19 was associated with modest increases in preterm delivery and intrapartum fetal distress.